Faktor-Faktor Sosial yang Memengaruhi Kepatuhan Masyarakat Surakarta terhadap Peraturan Lalu Lintas - Valentino Azendia Oktama Wijaya (Referendum : Jurnal Hukum Perdata dan Pidana, 2024)
The purpose of this article is to identify the factors that influence public compliance with traffic regulations and to find solutions for improving compliance. The data collection techniques used in this research include conducting surveys and field interviews, as well as gathering findings from various sources such as books, journals, and existing studies. As a country governed by the rule of law, Indonesia requires its citizens to abide by the laws in force, which is a fundamental principle in the context of law enforcement. The principle of the rule of law forms the foundation of Indonesia’s legal system, applying to all citizens and institutions, including the government. Compliance with the law is essential for maintaining order and harmony in society. Legal awareness is necessary for the comprehensive enforcement of regulations. Both the public and the government are responsible for understanding and complying with applicable laws, as well as fostering legal awareness in the community and future generations. The research findings reveal that the level of public compliance with traffic regulations in Surakarta is indeed influenced by several social factors such as education, honesty, and law enforcement. Based on these factors, solutions for improving public compliance with traffic regulations include strengthening law enforcement and enhancing the quality of education.